2015
DOI: 10.1371/journal.pone.0128589
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Functional Electrical Stimulation to Assist Ventilator Weaning in Acute Tetraplegia: A Cohort Study

Abstract: BackgroundSevere impairment of the major respiratory muscles resulting from tetraplegia reduces respiratory function, causing many people with tetraplegia to require mechanical ventilation during the acute stage of injury. Abdominal Functional Electrical Stimulation (AFES) can improve respiratory function in non-ventilated patients with sub-acute and chronic tetraplegia. The aim of this study was to investigate the clinical feasibility of using an AFES training program to improve respiratory function and assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
13
0
3
Order By: Relevance
“…Functional electrical stimulation (FES) is the application of a train of electrical pulses to a motor nerve, causing the associated muscle to contract. Transcutaneous FES of the abdominal muscles, termed abdominal FES, can improve respiratory function [1013] and assist ventilator weaning in spinal cord injury [12, 14]. Unlike inspiratory muscle training, which has been shown to improve weaning outcomes for difficult to wean patients [15, 16], abdominal FES does not require patient participation or cooperation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Functional electrical stimulation (FES) is the application of a train of electrical pulses to a motor nerve, causing the associated muscle to contract. Transcutaneous FES of the abdominal muscles, termed abdominal FES, can improve respiratory function [1013] and assist ventilator weaning in spinal cord injury [12, 14]. Unlike inspiratory muscle training, which has been shown to improve weaning outcomes for difficult to wean patients [15, 16], abdominal FES does not require patient participation or cooperation [16].…”
Section: Introductionmentioning
confidence: 99%
“…While outside the scope of this review, two articles have also reported that Abdominal FES can be used to assist ventilator weaning for patients with SCI. 46,47 Further research may indicate that this intervention is suitable for other ventilator dependent patient groups. Finally, Butler et al 2 and Lin et al 32 showed that combining Abdominal FES with an abdominal binder led to an acute increase in CPF, with Lin et al finding that for 12 tetraplegic patients this increase was significantly greater than that achieved using the binder alone.…”
Section: Future Researchmentioning
confidence: 99%
“…conforme segue a tabela 1. A técnica é clinicamente viável para pacientes tetraplégicos, especialmente aos dependentes de ventilador agudo, pois desencadeia uma melhora significativa da função respiratória, permitindo que o paciente deixa de usar mais rápido a ventilação mecânica (MCCAUGHEY et al, 2015).…”
Section: Resultsunclassified